Przewalski’s Horse (Equus ferus przewalskii) Re-introduction in the Great Gobi B Strictly Protected Area: from Species to Ecosystem Conservation - Kaczensky, P. (2007)
The Przewalski’s horse (Equus ferus przewalskii Poljakov, 1881), or “Takhi” in Mongolian, became extinct in the wild by the mid 1960’s. The last recorded sightings of Przewalski’s horses occurred in the Dzungarian Gobi desert in SW Mongolia, today’s Great Gobi B Strictly Protected Area (SPA). A re-introduction program was initiated in 1992 and the first group of captive-born Przewalski’s horses was airlifted to the SPA. Given the logistical challenges associated with such a venture, the initial project focus has been on transport logistics and the well-being of the re-introduced horses. Today, conservation efforts are spread over the entire protected area. Present day efforts include other mammals, vegetation and the local people. Due to its important symbolic value in Mongolian culture, the Przewalski’s horse became an important flagship species for the protected area’s conservation and management.